"I Can't Go to School and Leave Her in So Much Pain": Educational Shortfalls Among Adolescent 'Young Carers' in the South African AIDS Epidemic - Cluver, L; Operario, D; Lane, T; Kganakga, M (SAGE Publications, 2011)
"I go to the hospital with my mother when she is sick. I can't go to school and leave her in so much pain. I won't concentrate." Millions of adolescents live with AIDS-affected parents or primary caregivers. Little is known about educational impacts of living in an AIDS-affected home, or of acting as a "young carer" in the context of AIDS. This study combined qualitative and quantitative methods to determine educational impacts of household AIDS-sickness and other-sickness. Six hundred and fifty-nine adolescents (aged 10-20) were interviewed in high-poverty areas of urban and rural South Africa. Qualitative findings identified three major themes of missing school, being hungry at school, and concentration problems due to worry about the sick person. In quantitative analyses, living in an AIDS-affected home predicted all these three outcomes (p>.001) compared to homes affected by other sickness and to healthy homes, and independent of sociodemographic cofactors. This study demonstrates that familial AIDS-sickness is associated with negative educational impacts for adolescents. It is important that policies are developed to support young people in these circumstances to continue with their education. © The Author(s) 2012.